2012
DOI: 10.1145/2361256.2361259
|View full text |Cite
|
Sign up to set email alerts
|

Credit Rating Change Modeling Using News and Financial Ratios

Abstract: Credit ratings convey credit risk information to participants in financial markets, including investors, issuers, intermediaries, and regulators. Accurate credit rating information plays a crucial role in supporting sound financial decision-making processes. Most previous studies on credit rating modeling are based on accounting and market information. Text data are largely ignored despite the potential benefit of conveying timely information regarding a firm’s outlook. To leverage the additional information i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Cecchini et al (2010) extract concept scores from annual reports in order to develop a financial ontology discriminating between bankrupt/non-bankrupt companies. Lu et al (2012) employ sentiment analysis on the database of news articles. Their results show that topic-specific negative sentiment is more important for future credit rating changes compared with positive sentiment.…”
Section: Forecasting Financial Performance Using Text Information -mentioning
confidence: 99%
“…Cecchini et al (2010) extract concept scores from annual reports in order to develop a financial ontology discriminating between bankrupt/non-bankrupt companies. Lu et al (2012) employ sentiment analysis on the database of news articles. Their results show that topic-specific negative sentiment is more important for future credit rating changes compared with positive sentiment.…”
Section: Forecasting Financial Performance Using Text Information -mentioning
confidence: 99%
“…Regarding the central findings of the identified papers, the importance of the sentiment extracted from financial news for CRA could be shown quite consistently in varying research setups (Janner and Schmidt 2015;Liebmann et al 2016;Lu et al 2012;Norden 2017). The same applies to the volume of news (Tsai et al 2016).…”
Section: Results Analysismentioning
confidence: 78%
“…Therefore, they concluded that CRAs had a significant reaction to the information from the newspapers. Lu et al (2012) revealed that news was helpful to predict future credit ratings, implying that CRAs significantly reacted to the coverages in the newspaper. In this article, we will extend the previous literature to investigate the attitudes of CRAs to the financial news on the internet.…”
Section: Literaturementioning
confidence: 99%